Konsumerisme Dakwah Digital Ustadz Hanan Attaqi pada Akun Instagram @kata_uha - Mubarok, Muchammad Wildanil (Journal of Islamic Communication Studies, 2026)
The development of digital da'wah on Instagram has raised academic concerns regarding the transformation of religious messages into commodified cultural products, where spiritual values are no longer merely conveyed as transcendental teachings but are packaged and consumed like visual commodities within the ecosystem of platform capitalism. This study aims to identify and analyze the signifiers and signifieds in the da'wah content of @kata_uha that lead to practices of religious consumerism, reveal the cultural myths constructed through the visual representation of digital da'wah, and provide a critical perspective on the implications of religious commodification for Generation Z's understanding and practice of religion. A qualitative research method using Roland Barthes' semiotic content analysis was applied to 215 content pieces from the January-March 2025 period, where percentages were obtained through the quantification of the frequency of sign occurrences at each level of meaning based on predetermined categorization, involving two independent coders to ensure reliability. The findings reveal three main results: first, at the denotative level, da'wah content demonstrates a high degree of visual aesthetic standardization (95% consistent templates, 87% standardized typography, 73% pastel color palettes) following the logic of the creative industry; second, at the connotative level, spirituality is packaged as a digital lifestyle commodity with 83% integration of religious symbols and lifestyle elements, and 65% use of spiritual productivity narratives; third, at the mythical level, spiritual consumerism is constructed where 78% of the audience focuses on aesthetics over substance, 67% reduce religious experience to content consumption, and 45% of content contains monetization. The study concludes that digital da'wah has transformed into a product of the culture industry that alienates the substantive meaning of religion through the naturalization of platform capitalism logic. A critical approach and content production ethics are required to maintain the transformative function of da'wah in the digital era.